Introduction to the Nonprofit Sector - Mason, Dyana P. (Open textbook library., 2022)
Nonprofit organizations are on the front lines in communities, providing an important foundation for the social safety net in the United States and around the world. They also provide places where people can gather, share ideas and build community. They often accomplish amazing feats with few resources. This book was designed to be used in an undergraduate-level introductory course in the nonprofit sector. It provides an overview of the vocabulary used in defining the work of nonprofit organizations, topics of interest to nonprofit managers, and describes the primary roles nonprofits play in American (and to a lesser extent international) communities. The book also considers the growing numbers and influence of social enterprises and other “social innovation” organizations. Throughout, it brings in leading themes of accountability, ethics and obligations facing many nonprofit organizations as they go about their work – challenges that should be well understood by anyone interested in becoming a leader in the nonprofit sector.